2002
DOI: 10.1111/j.1749-6632.2002.tb04169.x
|View full text |Cite
|
Sign up to set email alerts
|

Calpain Upregulation and Neuron Death in Spinal Cord of MPTP‐Induced Parkinsonism in Mice

Abstract: Parkinson's disease (PD) is a neurodegenerative disorder resulting in slowness, tremors, and imbalance. Treatment of mice with 1‐methyl‐4‐phenyl‐1,2,3,6 tetrahydropyridine (MPTP) is one of several models used to mimic PD in humans. Administration of MPTP leads to the production of 1‐methyl‐4‐phenyl‐2,3 dihydropyridinium (MPP+). MPP+ is taken up by dopaminergic neurons, causing mitochondrial dysfunction and cell death. Because calpain is involved in neuronal cell death and mitochondrial dysfunction, we examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 40 publications
3
25
0
Order By: Relevance
“…Additionally, based on the dosing issue, reported above, some studies, looking at MPTP neurotoxicity on spinal cord were carried out using MPTP at dose/dosing less effective compared with those used here. This is the case of the following papers: Chera et al (2002): 10 mg/kg  1; Chera et al (2004); Samantaray et al (2008a,b): 50 mg/kg  1. Finally, this is the first study which was designed to quantify directly a potential motor neuron loss induced by MPTP.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Additionally, based on the dosing issue, reported above, some studies, looking at MPTP neurotoxicity on spinal cord were carried out using MPTP at dose/dosing less effective compared with those used here. This is the case of the following papers: Chera et al (2002): 10 mg/kg  1; Chera et al (2004); Samantaray et al (2008a,b): 50 mg/kg  1. Finally, this is the first study which was designed to quantify directly a potential motor neuron loss induced by MPTP.…”
Section: Discussionmentioning
confidence: 93%
“…Finally, this is the first study which was designed to quantify directly a potential motor neuron loss induced by MPTP. In fact, the few previous studies were based on indirect parameters, such as cleaved caspase-3 (Samantaray et al, 2008b) or 76 kDa calpain activation (Chera et al, 2002). This indicates that, just like DA neurons, MPTP neurotoxicity on spinal motor neurons depends on dose and dosing.…”
Section: Discussionmentioning
confidence: 98%
“…Focus of the present study was to determine whether intrinsic mitochondrial pathway of apoptosis coupled to aberrant intracellular Ca 2+ -homeostatsis and activation of proteolytic enzymes calpain and caspase-3 was involved in the process of motoneuron damage and death, as previously found in brain and spinal cord of animals with experimental parkinsonism (Ray et al, 2000; Chera et al, 2002, 2004; Crocker et al, 2003; Samantaray et al, 2006, 2007, 2008c). Calpeptin, a cell-permeable peptide aldehyde inhibitor of calpain, was examined for its efficacy to render cytoprotection.…”
Section: Introductionmentioning
confidence: 93%
“…The same authors showed TUNEL positive neurons (Samantaray et al, 2008b) and increased levels of active 76 kDa calpain (Chera et al, 2004;Samantaray et al, 2008a) throughout dorsal and ventral horn of lumbar spinal cord, from mice treated with MPTP, a neurotoxin which induces parkinsonism and neurodegeneration when it is oxidized in its drawn neurotoxin 1-methyl-4-phenylpyridinium ion (MPP + ) (Chiba et al, 1984;Markey et al, 1984). Calpain mediated neuronal death had been shown also in cultured spinal motoneurons exposed to MPP + or rotenone (Samantaray et al, 2008a), highlighting the role of calpain in mediating MPTP or rotenone induced neuronal death in the mice spinal cord (Ray et al, 2000;Chera et al, 2002Chera et al, , 2004.…”
Section: Degeneration Of Spinal Cord In Neurotoxin Induced Parkinsonismsmentioning
confidence: 96%